Un mot pour convaincre. De l’impact du mot « libéral » en politique à l’exemple de la campagne référendaire sur le Net - Jereczek-Lipińska, Joanna (Neophilologica, 2007)
The main topic of this paper deals with the pragmatic-semantic analysis of political speeches on the internet. It aims at examining the different uses of the word “libéral” and its derivatives within the Constitution Treaty for Europe on political blogs during the referendum campaign. It studies the meaning of the word “libéral” according to its various uses and analyzes the semantic evolution of this concept in a syntagmatic perspective. This study is based on a corpus of political blogs collected from January to June 2005.